Economic Efficiency of Smallholders Oil Palm Plantations in Lubuk Barumun District Padang Lawas Regency, North Sumatera - Simatupang, Jones; Siregar, M. Akbar; Sibuea, Mhd. Buhari (ITScience (Information Technology and Science), 2025)
This study was conducted to analyse the economic efficiency of smallholder oil palm plantations and the socioeconomic factors that affect them. The study area was purposively selected because it is the sub-district with the largest area of smallholder oil palm plantations in Padang Lawas Regency, with the largest area of smallholder oil palm plantations on the West Coast of North Sumatra Province. The study sample was determined using quota sampling, with 150 samples drawn from Aek Lancat Village and Pagaran Mompang Village, each with 75 samples. Data analysis methods used: Data Envelopment Analysis and Censored Tobit Regression Analysis for smallholder oil palm plantation management data for 2023. The results showed that the majority (85.33%) of smallholder oil palm plantations were not economically efficient, with an average economic efficiency value of 0.8789. Factors such as gender, farming experience, family size, type of seed used, distance from the farmer's residence to the input market, and experience in applying organic fertiliser significantly affected the economic efficiency of smallholder oil palm plantations. Meanwhile, socioeconomic factors such as age, education, the number of productive oil palm plants cultivated, access to credit, experience in participating in farmer organisations, and farmers' experience in using information and technology facilities related to farming management have no significant effect on the economic efficiency of smallholder oil palm plantations.